(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Iris Murdoch’s interest in human relationships may best be seen in the light of her moral philosophy. Her novels amply illustrates the link she sees between moral philosophy, human relationships and it is not by chance that she elucidates many of them through relationships between people. The concepts of internal struggle as a moral activity, of freedom and of love all share one important pre-requisite, which is attention – attention to the surrounding world and particularly attention to other people.